A typology of Goal-Source marking in transfer events. - Kittilä, Seppo (Studies in Language, 2022)
This paper discusses the coding of Goals and Sources from a cross-linguistic perspective and proposes a formal-functional typology based on how animacy and direction affect their coding. The proposed typology comprises three types; Goal vs. Source-languages, animacy and direction-languages, and variable types. The paper shows that the coding of Goals and Sources is primarily conditioned by their semantic roles (by the direction of transfer/motion), but animacy makes an important contribution in some languages as well. Moreover, the paper will also show that animacy affects the coding of Goals more drastically than it affects the coding of Sources. Goals and Sources differ from each other also in that Goals are more often coded by cases, while Sources are usually more peripheral participants and they are thus often marked by adpositions. One of the proposed reasons for this is found in the goal-oriented nature of humans.